The early reception and appropriation of the apostle Peter (60-800 ce) : the anchors of the fisherman - Dijkstra, Roald, 1985- (Euhormos: Greco-Roman Studies in Anchoring Innovation;, 2020)
"The apostle Peter gradually became one of the most famous figures of the ancient world. His almost undisputed reputation made the disciple an exquisite anchor by which new practices within and outside the Church could be established, including innovations in fields as diverse as architecture, art, cult, epigraphy, liturgy, poetry and politics. This interdisciplinary volume inquires the way in which the figure of Peter functioned as an anchor for various people from different periods and geographical areas. The concept of Anchoring Innovation is used to investigate the history of the reception of the apostle Peter from the first century up to Charlemagne, revealing as much about Peter as about the context in which this reception took place. Contributors are: Régis Burnet, John R. Curran, Roald Dijkstra, Jutta Dresken-Weiland, Kristina Friedrichs, Olivier Hekster, Annewies van den Hoek, Mark Humphries, Markus Löx, Thomas F. X. Noble, Els Rose, Carl P. E. Springer, Alan Thacker".